PENGARUH VARIASI ARUS PADA PROSES LAS TIG DAN VARIASI PUTARAN PADA PROSES FSW TERHADAP SIFAT MEKANIK DAN KOROSI SAMBUNGAN LAS TAK SEJENIS ALUMINIUM PADUAN 5083 DAN 6061-T6 - , Riswanda ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Dissimilar metal joint such as 5083 and 6061 - T6 aluminum alloys is often found in the structure or framework of trains, ships, bridges and oil-platform and structure of buildings. However, dissimilar metal welding relatively more difficult to do because of differences in thermophysical properties and metallurgy. This research aims to conduct a study of mechanical properties (tensile streng, hardness and microstructure) and corrosion to the effects of heat input expressed in current (100, 120 and 140 A) for TIG welding process, and rotation (1200, 1400 and 1600 rpm) for FSW process on dissimilar weld joint of 5083 and series 6061-T6 aluminum alloy. FSW and TIG welding processes was carried out on butt joint with plate size 300x100x3 mm and 300 mm long. Parameters for the TIG welding process are current variations of 100, 120 and 140 A at voltage of 20 V, whereas the FSW welding process uses variation of tools rotation those are 1200, 1400 and 1600 rpm with welding speed of 4 mm / min. Tests performed include visual observations, microstructure photographs, hardness and tensile test and corrosion. The results show that in general the TIG welding process is still better than the FSW welding process. The average microhardness in the weld metal of FSW process is 46.42 kg/mm2. This result is far below the TIG welding process, that is 73.83 kg/mm2. The highest tensile strength of FSW welding on 1600 rpm parameter is 151 MPa, but it is still lower than the highest tensile strength of TIG welding on the current 120 A, that is 201 MPa. Corrosion rate of TIG welding process is 0.0273 mm/yr and it is higher than that of FSW process, that is 0.0261 mm / yr.